Acc. Sc. Torino - Atti Sc. Fis. 140 (2006), Xx-Xx. Teoria Dei Numeri
Acc. Sc. Torino - Atti Sc. Fis. 140 (2006), Xx-Xx. Teoria Dei Numeri
Acc. Sc. Torino - Atti Sc. Fis. 140 (2006), Xx-Xx. Teoria Dei Numeri
1. Introduction
The Pell and Pell-Lucas sequences Pn and Qn are defined by the recurrence
relations
P0 = 0, P1 = 2, Pn = 2 Pn−1 + Pn−2 for n > 2,
and
Q0 = 2, Q1 = 2, Qn = 2 Qn−1 + Qn−2 for n > 2.
The numbers Qk make the integer sequence A002203 from [10] while the
numbers 12 Pk make A000129.
In this paper we prove twentyfour formulas for sums of a finite number
of consecutive terms of various integer sequences related to the Pell num-
bers. More precisely, for any integers k ≥ 0 and m ≥ 0 we consider the sum
1
Kopernikova 7, 10010 Zagreb, Croatia. E-mail: cerin@math.hr
2
Dipartimento di Matematica, Università di Torino, via C. Alberto 10, 10123 Torino,
Italy. E-mail: gianella@dm.unito.it
AMS 2000 Math. Subject Classification: Primary 11B39, 11Y55, 05A19.
Key words and phrases. Pell numbers, Pell-Lucas numbers, integer sequences, sum
of squares, sums of products.
2 ZVONKO ČERIN E GIAN MARIO GIANELLA
Pm
i=0 Pk+i and show that it can be evaluated as 12 Qk+m + Pk+m − 12 Qk .
In other words, we discover the formula for the sum of m + 1 consecutive
members of the Pell sequence. Then we accomplish the same thing for even
and for odd Pell numbers, for their squares and for six kinds of products of
adjacent Pell numbers. Finally, we treat also the alternatingPsums for those
sequences. For example, we prove that the alternating sum m i
i=0 (−1) Pk+i
m 1 1
is equal to (−1) 2 Qk+m − 2 Qk + Pk .
These formulas for sums have been discovered with the help of a PC com-
puter and all algebraic identities needed for the verification of our theorems
can be easily checked in either Derive, Mathematica or Maple V. Running
times of all these calculations are in the range of a few seconds.
Similar results for Fibonacci, Lucas and Pell-Lucas numbers have recently
been discovered in papers [1], [2], [3], [4] and [5]. They improved some results
in [7].
2. Statements of results
The best method to sum finitely many consecutive integers
k + (k + 1) + (k + 2) + · · · + (k + n)
is to group the initial number k and use the formula for the sum of the first
n natural numbers. Hence, the above sum is
n(n + 1) (n + 1)(2k + n)
k(n + 1) + = .
2 2
In this paper our first goal is to show that the analogous explicit formula
exists for the sum of finitely many consecutive members of the Pell integer
sequence.
Pm In other words, we first want to find the formula for the sum
i=0 k+i when m ≥ 0 and k ≥ 0 are integers.
P
We use the symbols N∗ = {0, 1, 2, 3, 4, . . . } for all natural numbers (with
zero included) and N∗∗ for the product N∗ × N∗ .
m
X 1
P2k+2i = [Q2k+2m + P2k+2m − Q2k + P2k ] =
2
i=0
1
= [Q2k+2m+2 − P2k+2m+2 + Q2k − P2k ] . (2.2)
2
m
X 1
P2k+2i+1 = [2 Q2k+2m + 3 P2k+2m − P2k ] . (2.3)
2
i=0
The alternating sums of consecutive Pell numbers, even Pell numbers and
odd Pell numbers are covered in the following theorem.
Theorem 3. For (m, k) ∈ N∗∗ the following equalities holds:
m
X 1 1
(−1)i Pk+i = (−1)m Qk+m − Qk + Pk . (2.4)
2 2
i=0
m
X
i m 1 1 1 1
(−1) P2k+2i = (−1) Q2k+2m + P2k+2m − Q2k + P2k . (2.5)
4 2 4 2
i=0
m
X
i m 3 1
(−1) P2k+2i+1 = (−1) Q2k+2m + P2k+2m + Q2k . (2.6)
4 4
i=0
The sums of squares of consecutive Pell numbers, even Pell numbers and
odd Pell numbers are treated in the following theorem.
Theorem 4. For (m, k) ∈ N∗∗ the following equalities holds:
m
X
2 1 1 1 1 (−1)k+m + (−1)k
Pk+i = Q2k+2m + P2k+2m + Qk − Pk − . (2.7)
4 2 4 2 2
i=0
m
X
2 1 3 1 3
P2k+2i = Q4k+4m + P4k+4m + Q4k − P4k − m − 1. (2.8)
4 8 4 8
i=0
m
X
2 3 17 1
P2k+2i+1 = Q4k+4m + P4k+4m − P4k + m + 1. (2.9)
2 8 8
i=0
m
X
P2k+4i P2k+4i+2 =
i=0
35 33 1 1
Q4k+8m + P4k+8m + Q4k − P4k − 3(m + 1). (2.17)
24 16 24 16
m
X
P2k+4i+1 P2k+4i+3 =
i=0
17 577 1
Q4k+8m + P4k+8m − P4k + 3(m + 1). (2.18)
2 48 48
The last six formulas cover the alternating forms of the relations from the
previous theorem.
Theorem 7. For (m, k) ∈ N∗∗ the following equalities holds:
m
X
(−1)i Pk+i Pk+i+1 =
i=0
m 1 3 1
(−1) Q2k+2m + P2k+2m + P2k − (−1)k (m + 1). (2.19)
2 4 4
m
X
(−1)i Pk+2i Pk+2i+1 =
i=0
(−1)k (1 + (−1)m )
m 7 5 1 1
(−1) Q2k+4m + P2k+4m − Q2k + P2k − . (2.20)
12 6 12 6 2
m
X
(−1)i P2k+2i P2k+2i+1 =
i=0
1 + (−1)m
7 5 1 1
(−1)m Q4k+4m + P4k+4m − Q4k + P4k − . (2.21)
12 6 12 6 2
m
X
(−1)i P2k+2i+1 P2k+2i+2 =
i=0
1 + (−1)m
m 41 29 1 1
(−1) Q4k+4m + P4k+4m + Q4k + P4k + . (2.22)
12 6 12 6 2
m
X
(−1)i P2k+4i P2k+4i+2 =
i=0
1 + (−1)m
m 99 35 3 1
(−1) Q4k+8m + P4k+8m + Q4k − P4k −3 . (2.23)
68 17 68 17 2
6 ZVONKO ČERIN E GIAN MARIO GIANELLA
m
X
(−1)i P2k+4i+1 P2k+4i+3 =
i=0
1 + (−1)m
m 577 1
(−1) Q4k+8m + 12 P4k+8m + Q4k + 3 . (2.24)
68 68 2
4. Proof of Theorem 1
The formula (2.1) clearly holds when m = 0. If we assume that it holds
for m = r, then we have
r+1
X r
X
Pk+i = Pk+i + Pk+r+1 =
i=0 i=0
1 1 1 1
Qk+r + Pk+r − Qk + Pk+r+1 = Qk+r+1 + Pk+r+1 − Qk ,
2 2 2 2
where the last step uses the formula Qn+1 − Qn = 2 Pn for n = k + r. Hence,
(2.1) is true also for m = r + 1 and the proof by induction√ is complete. √
The following direct proof is even
√ simpler. Let α = 1 + 2 and β = 1 − 2.
Note that α + β = 2, α − β = 2 2 and α · β = −1 so that the numbers α and
j −β j ) j j
β are solutions of the equation x2 − 2 x − 1 = 0. Since Pj = 2(αα−β = α √−β
2
and Qj = αj + β j we have
m m
X X αk+i − β k+i
Pk+i = √ =
i=0 i=0
2
m+1 − 1 m+1 − 1
k+m+1
− αk β k+m+1 − β k
1 k α k β 1 α
√ α −β =√ √ − √
2 α−1 β−1 2 2 − 2
1 h k+m+1 i 1
= α + β k+m+1 − αk + β k = (Qk+m+1 − Qk ) .
2 2
ON SUMS OF PELL NUMBERS 7
5. Proof of (2.2)
The formula (2.2) clearly holds when m = 0. If we assume that it holds
for m = r, then we have
r+1
X Xr
P2k+2i = P2k+2i + P2k+2r+2 =
i=0 i=0
1
= [Q2k+2r + P2k+2r − Q2k + P2k ] + P2k+2r+2 =
2
1
= Q2k+2(r+1) + P2k+2(r+1) − Q2k + P2k ,
2
where the last step uses the formula Qn+1 = Pn+1 + Pn . Hence, (2.2) is true
also for m = r + 1 and the proof by induction is complete.
The following direct proof is also simple. We have
m m
α2k+2i − β 2k+2i 2m+2 − 1 2m+2 − 1
X X 1 2k α 2k β
P2k+2i = √ = √ α −β
2 2 α2 − 1 β2 − 1
i=0 i=0
1 α2k+2m+2 − α2k β 2k+2m+2 − β 2k
=√ √ − √ =
2 2+2 2 2−2 2
α2k+2m+2 + β 2k+2m+2 α2k+2m+2 − β 2k+2m+2 α2k − β 2k α2k + β 2k
− √ − √ +
2 2 2 2 2 2
1
= [Q2k+2m+2 − P2k+2m+2 − P2k + Q2k ] .
2
6. Proof of (2.4)
m m
X
i
X αk+i − β k+i
(−1) Pk+i = (−1)i √ =
i=0 i=0
2
1
m+1 − 1 m+1 − 1
k (−α) k (−β)
√ α −β =
2 −α − 1 −β − 1
αk − (−1)m+1 αk+m+1 β k − (−1)m+1 β k+m+1
1
√ − =
2 α+1 β +1
αk − β k αk + β k
k+m+1
− β k+m+1 αk+m+1 + β k+m+1
α
√ − + (−1)m √ −
2 2 2 2
1 1 1 1
= Pk − Qk +(−1)m Pk+m+1 − Qk+m+1 = Pk − Qk +(−1)m Qk+m.
2 2 2 2
8 ZVONKO ČERIN E GIAN MARIO GIANELLA
7. Proof of (2.7)
m m k+i 2
X
2
X α − β k+i
=
Pk+i √ =
i=0 i=0
2
m
α2k α2m+2 − 1 β 2k β 2m+2 − 1
X
k
+ − (α β) (α β)i =
2 α2 − 1 2 β2 − 1
i=0
α2k+2m+2 − α2k β 2k+2m+2 − β 2k (−1)k+m + (−1)k
√ + √ − =
4+4 2 4−4 2 2
1 1 1 1 (−1)k+m + (−1)k
P2k+2m+2 − Q2k+2m+2 + Q2k − P2k − =
2 4 4 2 2
1 1 1 1 (−1)k+m + (−1)k
Q2k+2m + P2k+2m + Qk − Pk − ,
4 2 4 2 2
Qn+2 +Qn
where we used the fact that α β = −1 and the formula Pn+2 − Pn = 2
for n = 2k + 2m.
8. Proof of (2.10)
m m 2
αk+i − β k+i
X X
i 2 i
(−1) Pk+i = (−1) √ =
i=0 i=0
2
m
X α2k+2i − 2(α β)k+i + β 2k+2i
(−1)i =
2
i=0
m k m
α2k X 2 i β 2k X
X
(−α ) − (α β) (−α β) + k
(−β 2 )i =
i
2 2
i=0 i=0 i=0
α2k 2
(−α ) m+1 −1
β 2k 2
(−β ) m+1 −1
+ − (−1)k (m + 1) =
2 −α2 − 1 2 −β 2 − 1
α2k + (−1)m α2k+2m+2 β 2k + (−1)m β 2k+2m+2
√ + √ − (−1)k (m + 1) =
8+4 2 8−4 2
1 (−1)m
[Q2k − P2k ] − (−1)k (m + 1) + [Q2k+2m+2 − P2k+2m+2 ] =
4 4
(−1)m 1
[Q2k+2m + P2k+2m ] + [Q2k − P2k ] − (−1)k (m + 1),
4 4
where we used the formula Qn+2 − Pn+2 = Qn + Pn for n = 2k + 2m and
the fact that α β = −1.
ON SUMS OF PELL NUMBERS 9
9. Proof of (2.13)
m m k+i
− β k+i
k+i+1
− β k+i+1
X X α α
Pk+i Pk+i+1 = √ √ =
i=0 i=0
2 2
m m m
1 X 2k+2i+1 α + β X k+i 1 X 2k+2i+1
α − (α β) + β =
2 2 2
i=0 i=0 i=0
α2k+1
2 m+1
(−1)k+m + (−1)k β 2k+1 (β 2 )m+1 − 1
(α ) −1
− + =
2 α2 − 1 2 2 β2 − 1
α2k+2m+3 − α2k+1 β 2k+2m+3 − β 2k+1 (−1)k+m + (−1)k
√ + √ − =
4+4 2 4−4 2 2
1 1 1 1 (−1)k+m + (−1)k
P2k+2m+3 − Q2k+2m+3 − P2k+1 + Q2k+1 −
2 4 2 4 2
3 1 (−1) + (−1)k+m
k
= Q2k+2m + P2k+2m − Q2k − .
4 4 2
References
[1] Z. Čerin, Properties of odd and even terms of the Fibonacci sequence, Demonstratio
Mathematica, 39, No. 1, 2006, 55–60.
[2] Z. Čerin, On sums of squares of odd and even terms of the Lucas sequence, Proccedings
of the 11th Fibonacci Conference, (to appear).
[3] Z. Čerin, Some alternating sums of Lucas numbers, Central European Journal of
Mathematics 3, No. 1, 2005, 1 – 13.
[4] Z. Čerin, Alternating Sums of Fibonacci Products, Atti del Seminario Matematico e
Fisico dell’Università di Modena e Reggio Emilia, (to appear).
[5] Z. Čerin and G. M. Gianella, On sums of squares of Pell-Lucas numbers, INTEGERS:
Electronic Journal of Combinatorial Number Theory, 6 (2006), #A15.
[6] Z. Čerin and G. M. Gianella, Formulas for sums of squares and products of Pell
numbers, Accad. Sc. Torino - Atti Sci. Fis. 140 (2006), (to appear).
[7] V. Rajesh and G. Leversha, Some properties of odd terms of the Fibonacci sequence,
Mathematical Gazette, 88 2004, 85–86.
[8] R. Ram, Pell Numbers Formulae, http://users.tellurian.net/hsejar/maths/.
[9] T. Reix, Properties of Pell numbers modulo prime Fermat numbers, (preprint).
[10] N. Sloane, On-Line Encyclopedia of Integer Sequences, http://www.research.
att.com/∼njas/sequences/.